KERAGAMAN JENIS JAMUR YANG MENYERANG TANAMAN MAHONI (Swietenia Macrophylla KING.) DI KAMPUS UNIVERSITAS HASANUDDIN MAKASSAR, SULAWESI SELATAN (PERENNIAL, 2018)
Many Mahogany (Swietenia macrophylla King.) is used as the main tree in the area or the forestry industry plans. If the tree is planted monoculture, the mahogany stand has become highly vulnerable to pest and diseases, because monoculture tree plantations are an abundant food source for both organisms. This study aims to determine the types of fungi that attacking and cause disease in plant parts mahogany. The result showed that there are ten species of fungi that attack mahogany. Seven of them have been identified while the other cannot be identified. Fungi are attacked or negative associations in the roots, stem, leaves and fruits of plant mahogany. The seven species of fungi are Rhizopus arrhizus Fischer; Mucor racemosus Fres; Mycgone rosea Link; Absidia corymbifera (Cohn.) Sacc and Trotter; Monilia sitophila (Mont.) Sacc; Cladosporium spharospermeum Penzig; and Myrothecium verrucaria (Orig.). Fungi that attack the roots of the tree are A. corymbifera (Cohn.) Sacc and C. spharospermeum Penzig. M. rosea Link and M. sitophila (Mont.) Sacc attacking the leaf. R. arrhizus Fischer and M. verrucaria (Orig.) attacks the stems of trees while Mucor racemosus Fres. Attacking the fruit of mahogany. Fungi that cannot be identified are a fungus that attacks the stems and leaves. Key words: Switenia macrophylla King, Fungi